Antigen Cross-Priming of Cell-Associated Proteins is Enhanced by Macroautophagy within the Antigen Donor Cell - Albert, Matthew; Joubert, Pierre-Emmanuel (Frontiers in Immunology, 2012)
Phagocytosis of dying cells constitutes an importance mechanism of antigen capture for the cross-priming of CD8+ T cells. This process has been shown to be critical for achieving tumor and viral immunity. While most studies have focused on the mechanisms inherent in the dendritic cell that account for exogenous antigen accessing MHC I, several recent reports have highlighted the important contribution made by the antigen donor cell. Specifically, the cell stress and cell death pathways that precede antigen transfer are now known to impact cross-presentation and cross-priming. Herein, we review the current literature regarding a role for macro-autophagy within the antigen donor cell. Further examination of this point of immune regulation is warranted and may contribute to a better understanding of how to optimize immunotherapy for treatment of cancer and chronic infectious disease.